2010
DOI: 10.1074/jbc.m109.094425
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Subtypes Regulate CCCTC Binding Factor Affecting Corneal Epithelial Cell Fate

Abstract: CCCTC binding factor (CTCF) controls DNA imprinting, insulates important gene expression, and mediates growth factor-and stress-induced cell fate. However, regulatory mechanisms involved in intracellular CTCF activity are largely unknown. In this study, we show that epidermal growth factor (EGF)-induced increase and UV stress-induced decrease in CTCF activities mediate human corneal epithelial cell proliferation and apoptosis, respectively. CTCF is regulated by activation of different NF-B subtypes via stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Recent studies indicate that CTCF is involved in * This work was supported, in whole or in part, by National Institutes of Grants the regulation of cell migration in cancer cell proliferation, tumor suppression, and apoptosis (29 -31). In corneal epithelial cells, EGF-induced activation of the NF-B pathway regulates cell fate in a subtype-specific fashion through interactions with CTCF that function as a downstream component in the core transcriptional network (14,32). We found that, in corneal epithelial cells, CTCF is a targeted gene of the growth factor-induced pathways, including the Erk, AKT, and NF-B signaling cascades.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Recent studies indicate that CTCF is involved in * This work was supported, in whole or in part, by National Institutes of Grants the regulation of cell migration in cancer cell proliferation, tumor suppression, and apoptosis (29 -31). In corneal epithelial cells, EGF-induced activation of the NF-B pathway regulates cell fate in a subtype-specific fashion through interactions with CTCF that function as a downstream component in the core transcriptional network (14,32). We found that, in corneal epithelial cells, CTCF is a targeted gene of the growth factor-induced pathways, including the Erk, AKT, and NF-B signaling cascades.…”
mentioning
confidence: 85%
“…As demonstrated in human corneal epithelial cells, EGF elicits complex responses at early times by inducing specific cellular signaling pathways that transfer the signals to the nucleus and activate the transcription factor at later times (3,14,15,33,38). In previous studies, we found that EGF-induced formations of the NFB p65/p50 heterodimer and p50/50 homodimer activate CTCF transcription by binding to a B site located in the promoter region of the CTCF gene and that an increase in CTCF activity in corneal epithelial cells promotes cell motility and migration (14,17). These results indicate that NFB subtypes interact directly with the CTCF gene in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations